Low resistivity, p-type, N-Polar GaN achieved by chemical potential control. (1st August 2022) - Rathkanthiwar, Shashwat; Szymanski, Dennis; Khachariya, Dolar; Bagheri, Pegah; Kim, Ji Hyun; Mita, Seiji; Reddy, Pramod; Kohn, Erhard; Pavlidis, Spyridon; Kirste, Ronny; Collazo, Ramón; Sitar, Zlatko
Abstract: We report on low resistivity (1.1 Ω cm) in p-type bulk doping of N-polar GaN grown by metalorganic chemical vapor deposition. High nitrogen chemical potential growth, facilitated by high process supersaturation, was instrumental in reducing the incorporation of compensating oxygen as well as nitrogen-vacancy-related point defects. This was confirmed by photoluminescence studies and temperature-dependent Hall effect measurements. The suppressed compensation led to an order of magnitude improvement in p-type conductivity with the room-temperature hole concentration and mobility measuring 6 × 10 17 cm −3 and 9 cm 2 V −1 s −1, respectively. These results are paramount in the pathway towards N-polar GaN power and optoelectronic devices.